Implementasi manajemen pendidikan Islam di Madrasah Tsanawiyah Negeri 3 Sragen - Agustina, Kalista Eka; Shohib, Muhammad Wildan (Program Studi Magister Pendidikan Agama Islam, 2026)
This study examines the implementation of Islamic education curriculum management, along with its strengths and weaknesses, at MTs N 3 Sragen in aligning the national curriculum with the madrasah curriculum, particularly in the context of a dynamic curriculum. This article analyzes the process of implementing Islamic education management at MTs N 3 Sragen and identifies its strengths and weak-nesses. The research method used is qualitative with a field research approach. Data collection was conducted through in-depth interviews with the Vice Principal for Curriculum and Islamic Religious Education (PAI) teachers at MTs N 3 Sragen. The research results indicate that the implementation of Islamic education management at MTs N 3 Sragen is carried out systematically, based on the Qur’an and Sunnah, and is adaptive to changing times, guided by Ministerial Decrees (KMA) No. 183 and 184 of 2019. The strength of Islamic education management implementation at the madrasah lies in the in-tegration of religious moderation values with a modern approach, reflected in religious habit-forming programs and a holistic evaluation system. However, the madrasah faces significant challenges, includ-ing dichotomies in education, the readiness and competence of teaching staff, and resource constraints in developing integrated teaching modules. Abstrak Penelitian ini mengkaji pelaksanaan manajemen kurikulum pendidikan Islam, beserta kelebihan dan kekurangannya, di MTs N 3 Sragen dalam menyelaraskan kurikulum nasional dengan kurikulum madrasah, khususnya dalam konteks kurikulum dinamis. Artikel ini menganalisis proses implementasi manajemen pendidikan Islam di MTs N 3 Sragen serta mengidentifikasi kelebihan dan kekurangannya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan field research. Pengumpulan data dilakukan melalui wawancara mendalam dengan Wakil Kepala Sekolah Bidang Kurikulum dan guru Pendidikan Agama Islam (PAI) di MTs N 3 Sragen. Hasil penelitian menunjukkan bahwa implementasi manajemen pendidikan Islam di MTs N 3 Sragen dilakukan secara sistematis, berdasarkan Al-Qur’an dan Sunnah, serta adaptif terhadap perubahan zaman, dengan panduan Keputusan Menteri (KMA) Nomor 183 dan 184 Tahun 2019. Kelebihan implementasi manajemen pendidikan Islam di madrasah terletak pada integrasi nilai-nilai moderasi agama dengan pendekatan modern, yang tercermin dalam program pembiasaan religius dan sistem evaluasi holistik. Meskipun demikian, madrasah menghadapi tantangan yang signifikan, termasuk dikotomi dalam pendidikan, kesiapan dan kapabilitas SDM guru, serta keterbatasan sumber daya dalam menyusun modul ajar terintegrasi.